Comparing clonidine and dexmedetomidine effects in the treatment of opiate withdrawal syndrome in poisoned patients - Azadeh Memarian; Mahdiye Abiyarghamsari; Shahin Shadnia; Babak Mostafazadeh; Peyman Erfan Talab Evini; Mahdiye Golestani Fard; Mitra Rahimi (Medicina Clínica Práctica)
Background: While opiate withdrawal syndrome (OWS) typically resolves within a few weeks, the discomfort in the initial days after discontinuing opioid use is intense. In this study, we compared the effects of 2 drugs, clonidine and dexmedetomidine, for treating OWS in patients admitted to the Toxicology ICU at Loghman-e Hakim Hospital. Methods: We collected patient information for individuals diagnosed with OWS in this clinical trial study. Fifty-two patients, matched based on the type of drug use (methadone, opiate, heroin), were included and divided into 2 groups. We compared the clinical effects of 2 drugs, dexmedetomidine and clonidine, on OWS symptoms using the Clinical Opiate Withdrawal Scale (COWS). The dexmedetomidine group received a dosage of 0.5 mcg/kg/h continuous IV infusion; not to exceed 24 h, while the clonidine group received 1.2 mg per day for 24 h. We completed the COWS standard checklist and compared the results after 0, 12, and 24 h. Results: At Zero hours' patients who were administered dexmedetomidine had a significantly higher average COWS score of 0.684, compared to a score of 0.053 for patients who received clonidine (p-value=.000201). At the 12-h, the distinction between the 2 treatment groups was no longer statistically significant, as evidenced by a p-value of .162829 (dexmedetomidine: 0.105 vs. clonidine: 0.000). Conclusions: The results suggest that dexmedetomidine is superior to clonidine in reducing withdrawal symptoms. The study found that both medications had a significant decrease in COWS scores over time, indicating their effectiveness in alleviating withdrawal symptoms as time passed. Resumen: Antecedentes: si bien el síndrome de abstinencia de opiáceos (SOW) generalmente se resuelve en unas pocas semanas, el malestar en los primeros días después de suspender el uso de opioides es intenso. En este estudio, comparamos los efectos de dos fármacos, clonidina y dexmedetomidina, para el tratamiento del síndrome de abstinencia de opiáceos (SOW) en pacientes ingresados en la UCI de Toxicología del Hospital Loghman-e Hakim. Métodos: En este estudio clínico aleatorizado, se recopiló información de pacientes de personas diagnosticadas con síndrome de abstinencia de opiáceos. Se incluyeron y dividieron en dos grupos cincuenta y dos pacientes, emparejados según el tipo de consumo de drogas (metadona, opiáceos, heroína). Los efectos clínicos de dos fármacos, dexmedetomidina y clonidina, sobre los síntomas del síndrome de abstinencia de opiáceos se compararon mediante la Escala Clínica de Abstinencia de Opiáceos (COWS). El grupo de dexmedetomidina recibió una dosis de 0,5 mcg/kg/h en infusión intravenosa continua; no exceder las 24 horas, mientras que el grupo de clonidina recibió 1,2 mg/día repartidos durante 24 horas. La lista de verificación estándar COWS se completó y comparó a las 0, 12 y 24 horas. Resultados: En las horas cero, los pacientes a los que se les administró dexmedetomidina tuvieron una puntuación COWS promedio significativamente mayor, de 0,684, en comparación con una puntuación de 0,053 para los pacientes que recibieron clonidina (p = 0,000201). A las 12 horas, la distinción entre los dos grupos de tratamiento ya no era estadísticamente significativa, como lo demuestra un p de 0,162,829 (dexmedetomidina: 0,105 frente a clonidina: 0,000). Conclusiones: Los resultados sugieren que la dexmedetomidina es superior a la clonidina para reducir los síntomas de abstinencia. La investigación demostró una disminución significativa en las puntuaciones COWS de ambos medicamentos con el tiempo, lo que indica su eficacia para aliviar los síntomas de abstinencia conforme avanzaba el tiempo.